2011
DOI: 10.1002/path.2830
|View full text |Cite
|
Sign up to set email alerts
|

Stromal features are predictive of disease mortality in oral cancer patients

Abstract: Worldwide, approximately 405 000 cases of oral cancer (OSCC) are diagnosed each year, with a rising incidence in many countries. Despite advances in surgery and radiotherapy, which remain the standard treatment options, the mortality rate has remained largely unchanged for decades, with a 5-year survival rate of around 50%. OSCC is a heterogeneous disease, staged currently using the TNM classification, supplemented with pathological information from the primary tumour and loco-regional lymph nodes. Although pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
302
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(336 citation statements)
references
References 30 publications
30
302
3
1
Order By: Relevance
“…The intense SMA expression at the tumouradvancing front, was significantly associated with the N-stage and presence of nodal metastasis and its patterns are in keeping with previous studies (Kellermann et al, 2007;Surowiak et al, 2007;Marsh et al, 2011;Thode et al, 2011). The distribution of SMA immunoreactivity in the tumour stroma varies widely between different tumours and between different areas in the same tumour, and reflects heterogeneity (Vered et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The intense SMA expression at the tumouradvancing front, was significantly associated with the N-stage and presence of nodal metastasis and its patterns are in keeping with previous studies (Kellermann et al, 2007;Surowiak et al, 2007;Marsh et al, 2011;Thode et al, 2011). The distribution of SMA immunoreactivity in the tumour stroma varies widely between different tumours and between different areas in the same tumour, and reflects heterogeneity (Vered et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, a combined approach using both SMA and SERPINE1 expression at the advancing front showed greater ability to predict survival than expression of the individual proteins. The most recent and largest study of prognostic stromal features in OSCC reported a greater prognostic significance for SMA expression in the stroma of OSCC than the presence of ECS (Marsh et al, 2011). Our study, however, suggests that ECS is of greater prognostic value, but that SMA plus SERPINE1 expression in combination was highly significantly associated with adverse outcomes.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…4 In a number of different cancer types, stromal properties have demonstrated importance in disease identification, progression, and patient prognosis. [5][6][7][8][9][10][11][12] Given the pronounced desmoplastic reaction in pancreatic ductal adenocarcinoma, a large number of recent research efforts have focused on elucidating stroma-cancer interactions for both nuanced insight into disease progression and for potential diagnostic, prognostic, or therapeutic targets. 13 The dominant extracellular matrix component of most tumor stromas, including that of pancreatic ductal adenocarcinoma, is fibrillar collagen.…”
mentioning
confidence: 99%
“…Even with advancements in surgery and radiotherapy, mortality still is very high with a 5-year survival rate of only 50%. 11 The prognosis in the initial stages (I and II) is relatively good with surgery and/or radiotherapy. While in the 3 rd or 4 th stage of OSCC, combined surgery and radiotherapy or chemotherapy is the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%